Pengaruh Latihan Shooting untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Sepak Bola Kelas XII MA Nihayatul Amal Rawamerta - Saputra, Naldia Defa; Siswanto, Siswanto; Nugroho, Setio (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to prove the effectiveness of the exercise shooting skills in learning the game of football. This research is experimental with one-group-pretest and posttest design. The sampling technique was random sampling in order to obtain a sample of 36 students from MA Nihayatul Amal. The results showed that there was an increase in the posttest average score compared to the pretest of 3.03 and a significant increase. The increase occurred due to leg muscle strength training using the circuit method, namely the movement between posts. Thus, leg muscle strength training is effective in improving shooting ability in soccer games.